A Fast, Sensitive and Validated Analytical Method for Quantitation of Imidacloprid Pesticide Residual in Mangifera indica Matrix by LC-Tandem Mass Spectrometry (LC-ESI-MS/MS) - Patel, Meet; Patel, Alpesh; Prabhu, Padmaja; Pandya, Mayank (Asian Journal of Chemistry, 2022)
An accurate and precise analytical method was performed for the quantitation of imidacloprid pesticide residue in the matrix of Mangifera indica (alphonso), specific species of Indian mango of Valsad District, Gujarat. The validation of the analytical technique was carried out using UPLC-ESI-MS/MS and was done in accordance with the regulatory recommendations. The projected technique is based on QuEChERS Method with a mixture of diluents used followed by clean up with the PSA. Three concentration levels (0.50, 2.55 and 5.10 μg/kg) were used to validate the approach and the outcomes ranged between 70 to 120%, with relative standard deviations (% RSD) of ≤ 20%. The detection and quantification limits were derived at the concentration of 0.010 and 0.50 μg/kg, respectively with a significant %ME of 9.90%. The quantitation of imidacloprid pesticide residue in the mango matrix can be done at a lower quantification level by UPLC-ESI-MS/MS.